Complementing Business Training with Access to Finance: Evidence from SMEs in Kenya - Anik Ashraf; Elizabeth Lyons (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
In this paper, we study the complementarity between business training and access to financial capital for small and medium enterprises (SMEs) in Kenya. All participants in a business training program are offered training. One-third of participants are offered loans immediately after training (Concurrent Loan group), one-third are offered loans six weeks after training (Delayed Loan group), and the remaining third are offered loans after another four weeks (Control group). While a long delay between training and loans may reduce knowledge retention and application by SMEs in the presence of complementarity, concurrent access to loans and associated business spending may crowd out the entrepreneurs' attention from improving business practices. We find evidence for the latter in both intention-to-treat and treatment-on-the-treated estimates. While SMEs in both Control and Delayed Loan groups improve their business practices, SMEs in the Concurrent Loan group who take loans do not improve their practices at all. Moreover, entrepreneurs who take loans spend less time on their businesses and their business revenue falls. Our evidence is consistent with the entrepreneurs in our study using loans to substitute for their income.
Keywords: O12; L26; M53; 330; business training; access to finance